A sequential extraction procedure for particulate manganese and its application to coastal marine sediments - Lenstra, W.K.; Klomp, R.; Molema, F.; Behrends, T.; Slomp, C.P. (Chemical geology, 2021)
•A sequential extraction method for the speciation of particulate Mn is presented.•The method allows the simultaneous speciation of particulate Fe and Mn.•Bottom water redox conditions impact sediment Mn speciation.•Mn carbonates dominate in sediments subject to periodic bottom water redox change.•Mn oxides and/or Mn phosphates are Mn sinks in sediments with oxic bottom waters. An existing sequential extraction scheme for particulate iron (Fe) is evaluated for manganese (Mn) using a range of Mn standards. The scheme consists of 5 steps and quantifies 5 operationally defined Mn pools (1) poorly ordered Mn oxides and Mn phosphates (ascorbic acid extractable); (2) Mn carbonates and Mn sulfides (1M HCl extractable), (3 and 4) crystalline Mn oxides (citrate buffered dithionite and ammonium oxalate extractable, respectively) and (5) Mn associated with pyrite (concentrated HNO3 extractable). Application of the extraction scheme to coastal sediments from six locations (Black Sea, Baltic Sea, Bothnian Sea, Gulf of Mexico and Chesapeake Bay) highlights the dependency of sediment Mn partitioning on bottom water redox conditions. In sediments deposited in anoxic and sulfidic (euxinic) bottom waters, Mn is mostly present in Mn carbonates, pyrite and in non-reactive Mn forms, in approximately equal amounts. We find that in sediments deposited in periodically euxinic and hypoxic (oxygen <63μmolL−1) waters, Mn carbonates dominate over the two other fractions, and small amounts of Mn oxides are observed. In sediments deposited in oxygenated bottom waters, Mn oxides, Mn-rich vivianite-type minerals and Mn carbonates dominate and no pyrite-bound Mn is observed. A large advantage of the extraction scheme is that it quantifies sediment forms of Mn and Fe simultaneously. Given the role of Mn as a bottom water redox proxy, the separation of poorly ordered Mn oxides, carbonates and pyrite is of specific relevance.